The Inner Circle of Power on Twitter?: How Politicians and Journalists Form a Virtual Network Elite in Finland - Ruoho,Iiris (2019)
Top-level politicians and political journalists have been key actors in public discussion necessary for a democratic political system and transparent political decision-making. This article presents an empirical social network analysis showing the connections between Finnish top-level politicians and political journalists on Twitter and the construction of mediated political and media elites in this specific context. The article argues that there is a need to take seriously the Twitter as a medium and the new ways of networking provided by the digital, hybrid media environment in particular. The results of our empirical study suggest that it may even be relevant to talk about mediated elites, which have emerged under the new social condition created by the digitalization of media, culture, and society.